Transient anode voltage modeling of IGBT and its carrier lifetime dependence - Das, Avijit; Islam, Nazmul; Haq, Masud Ul; Khan, Ziaurrahman (© 2015 IEEE, 2018)
This conference paper was published in the IEEE Region 10 Conference, TENCON 2015; Holiday Inn, Sands Cotai CentralMacau; Macau; 1 November 2015 through 4 November 2015 [© 2015 IEEE] and the definite version is available at : http://doi.org/10.1109/TENCON.2015.7372970 The Journal's website is at: https://ieeexplore.ieee.org/document/7372970/